2011
DOI: 10.1188/11.onf.e365-e372
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Sleep in Pediatric Patients With Leukemia: The Potential Role of <i>Interleukin-6</i> (-174GC) and <i>Tumor Necrosis Factor</i> (-308GA) Polymorphism

Abstract: Disturbed sleep among pediatric patients with cancer is multifactoral and includes interactions among environment, medications, and genotype. Additional research should explore serum proinflammatory cytokine levels and the influence of mood and worry on sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
(48 reference statements)
0
17
0
Order By: Relevance
“…Such changes to sleep architecture may be responsible for the subjective experience of poor sleep quality and reports of increased awakenings. Older patient age and higher risk group have also been shown to contribute to slower dexamethasone clearance, which may contribute to some of the variabilities observed within steroid groups in the current study [40]. …”
Section: Discussionmentioning
confidence: 99%
“…Such changes to sleep architecture may be responsible for the subjective experience of poor sleep quality and reports of increased awakenings. Older patient age and higher risk group have also been shown to contribute to slower dexamethasone clearance, which may contribute to some of the variabilities observed within steroid groups in the current study [40]. …”
Section: Discussionmentioning
confidence: 99%
“…[39, 40] In studying this relationship in children undergoing steroid chemotherapy for ALL, Vallance, et al found a correlation between a polymorphism in the TNF gene (-308G>A) and steroid-associated sleep disruption. [41] In our study and presented in supporting information, we also investigated the effect of dexamethasone on melanin-concentrating hormone (MCH), an influential regulator of the ascending arousal system that controls the switch from REM sleep to NREM sleep; we found no evidence that dexamethasone affects MCH physiology (S1 Supplemental Methods, S1 Supplemental Results and S3 Fig). …”
Section: Discussionmentioning
confidence: 99%
“…They are noted to be increased in adults and children with obstructive sleep apnea and sleep insufficiency, and they are associated with daytime sleepiness. TNF-α and IL-1 meet the criteria as sleep-regulatory substances [24]. Single-nucleotide polymorphisms of TNF-α and IL-6 are associated with disturbed sleep in children with ALL [25].…”
Section: Discussionmentioning
confidence: 99%